If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 5) = 29 + -1x Reorder the terms: 3(5 + 2x) = 29 + -1x (5 * 3 + 2x * 3) = 29 + -1x (15 + 6x) = 29 + -1x Solving 15 + 6x = 29 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 15 + 6x + x = 29 + -1x + x Combine like terms: 6x + x = 7x 15 + 7x = 29 + -1x + x Combine like terms: -1x + x = 0 15 + 7x = 29 + 0 15 + 7x = 29 Add '-15' to each side of the equation. 15 + -15 + 7x = 29 + -15 Combine like terms: 15 + -15 = 0 0 + 7x = 29 + -15 7x = 29 + -15 Combine like terms: 29 + -15 = 14 7x = 14 Divide each side by '7'. x = 2 Simplifying x = 2
| 21=0.3(3-4x) | | 21=0.3(3-4) | | 21=0.393-40 | | 65=5(4-3x) | | 4x^2-8x-5=-5 | | 0.5(4-2x)=24 | | 5(3+2x)=25 | | 2x^2+2x+9=0 | | (2x+9)=33 | | 4x+2y+6z=36 | | 3x^2-4.7x+0.4=0 | | 15e=7e-19 | | 6v=16+13v | | 2x-4=6-3(-x+2) | | 6x^2+18x-24x=0 | | 3(x-3)-2(x-4)= | | 3-4n=11 | | 22-3f=2f | | 9y^2-24+11=0 | | t=14-2t | | 4t=15-13t | | x^3+3x^2-24x-3=0 | | 7n+26=5n | | 6.1+10.1q=4q | | 13p+54=7p | | 3x^3-15x^2+21x-5=0 | | 0.3c=25.9+4c | | 8.4d-23=13d | | 71-12=9a | | 4x-6=7x+3 | | x-(a+3)=a-2(a-x) | | 192-7x=29x+16 |